A new antispasmodic in obstetrics: The phloroglucinol-trimethoxybenzene association - Bachmann, Carlos (2015)
We studied 150 patients in the Maternity Hospital of Lima to appreciate the variations clinically pain with phloroglucinol trimethoxybenzene association, childbirth and postpartum. Doses of 120 mg were used. phloroglucinol and 40 mg. of trimethoxybenzene orally in 75 patients with immediate postpartum, 24 and 48 hours after the intravenous route and in 75 pregnant women in labor at a dose of 40 mg. phloroglucinol and 40 mg. of trimethoxybenzene. The results were: Reduction of pain in 66% within the first 24 hours for patients taking the drug immediately after childbirth, disappearing completely after 48 hours of treatment in patients with postpartum 24 hours pain decreased 86%, with full effect within 48 hours and in patients with postpartum 48 hours in total improvement was observed at 24 hours. In pregnant women in labor, pain decreased significantly in 70%. The remaining 30% did not experience any improvement despite a second dose was applied without any positive results. It was observed that after applying the drug, dilation and descent of the presentation was held in lower than expected, 80% time.